2022
DOI: 10.3727/154427221x16245632411908
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Socioeconomic Impacts of A Women's Major Sporting Event in Africa

Abstract: Major sports events have emerged as an important destination development tool for many developing countries in sub-Saharan Africa. This study aimed to assess the socioeconomic impacts of the 2016 Women African Cup of Nations (WAFCON) hosted in Cameroon. Taking the hosting cities (Limbe and Yaounde) as the case study sites, the study utilized a mixed-methods research approach. The data emerged from the 759 questionnaires distributed to the event attendees and 10 interviews with key informants. The study showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In 2016, Cameroon hosted the 12th edition of the Women's AFCON. These types of major sports events not only promise media attention for the Cameroon nation brand, but also create opportunities for inbound tourism and other sport business related benefits Achu et al, 2022). Clarke (2022) reports that economically, businesses in Cameroon all have their eyes on a revival and boost in revenue through the 2022 AFCON tournament.…”
Section: The Cameroon Sport Brandmentioning
confidence: 99%
“…In 2016, Cameroon hosted the 12th edition of the Women's AFCON. These types of major sports events not only promise media attention for the Cameroon nation brand, but also create opportunities for inbound tourism and other sport business related benefits Achu et al, 2022). Clarke (2022) reports that economically, businesses in Cameroon all have their eyes on a revival and boost in revenue through the 2022 AFCON tournament.…”
Section: The Cameroon Sport Brandmentioning
confidence: 99%
“…In the context of this study, football (soccer) is one of the fastest-growing and most popular sport in Cameroon (Tichaawa et al, 2018;Nyikana and Tichaawa, 2023) and has commonly been linked to an important part of socio-economic benefits, including nation-building for the country as many studies have shown Nyikana & Tichaawa, 2018a, b, c;Nyikana and Tichaawa, 2020;Daniels and Tichaawa, 2021;Achu et al, 2022;Tichaawa, 2022, Acha-Anyi, 2023a, b). The recent 2021 Africa Cup of Nations (AFCON) tournament was hosted by Cameroon and this event has proven the nation's capabilities to successfully host major sporting spectacles.…”
Section: Introductionmentioning
confidence: 99%